AN AUDIT OF THE PREVALENCE AND CHARACTERISTICS OF ADVANCE CARE PLANNING FOR PATIENTS FROM RESIDENTIAL AGED CARE FACILITIES (RACFS) REFERRED TO THE MOBILE ASSESSMENT AND TREATMENT SERVICE (MATS). Issue 2 (1st June 2013) - Jafari, B; Austin, N; Lemke, R; Poojary, S
Abstract : Background: Advance Care Planning (ACP) ensures recognition of a person's wishes and promotes autonomy, however, completion and implementation has been a challenge. Aim: To assess the prevalence of ACP in patients from Residential Aged Care Facilities (RACFs) referred to the 'Residential In-reach' service of Alfred Health known as Mobile Assessment and Treatment Service (MATS), and to assess how the process of ACP has been approached by the mangers of those facilities. Methods: Part A: Prospective audit of documentation of ACP for 100 patients referred to MATS Part B: De-identified, paper-based surveys of the managers of the RACFs where the patients from part A of the study were residing. Results: Part A: The prevalence of ACP, Medical Enduring Power Of Attorney and 'Not for Resuscitation' form were 38%, 37% and 35%, respectively. Patients with ACP or a separate 'NFR' form were significantly more likely to be living in high care compared to low care facilities (79% vs 21%, p=0.049 and 80% vs 20%, p=0.032, respectively). Part B: There was a significant inconsistency between the facilities with regards to 'facility requirements' for ACP, 'person responsible', 'documentation' and 'GP involvement'. Discussion: This study found a low prevalence of ACP, MEPOA and 'NFR' form in patients from RACFs referred to MATS. There was also lack of a systematic approach in the process of ACP. Conclusion: There is a need for structured policy coupled with appropriate funding as well as further education of both public and health professionals.